Evaluation of ABO and Rh Blood Group Frequencies in the Population of Sirte City, Libya - Fouz Abdul Aziz,; Mohamed Elhouni, (AlQalam Journal of Medical and Applied Sciences, 2025)
The distribution of ABO blood groups and Rh factors has been extensively studied, with findings typically similar on the most common blood group, although with regional variations in proportions. This study aimed to assess the prevalence of ABO and Rh blood group systems in the population of Sirte city. Data from 7,127 individuals (4,064 males and 3,063 females) were collected from the archives of the Sirte Passport Center. These records were compiled over intermittent intervals and represented residents from various areas within the city. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) software. The analysis revealed that blood group O was the most prevalent (54.6%), followed by group A (28.0%), group B (14%), and group AB (3.2%). Additionally, 11.3% of the population was Rh-negative. In Sirte, the distribution of ABO and Rh blood groups followed the pattern: O > A > B > AB, with Rh-positive being the predominant group. These findings are consistent with previous studies conducted in other Libyan cities.